The Take-Off of Sustainability: Evaluating Sustainable Airport Performance - Hendra Soemanto; M. Noor Salim; Dudi Permana; Singmin Johanes Lo (Eduvest - Journal of Universal Studies, 2025)
The aviation industry plays a vital role in our interconnected world. However, its growth also comes with environmental concerns. Airports, as air travel hubs embrace sustainability. This is to minimize their ecological impact. This effort involves looking beyond airplanes at the entire airport ecosystem. It includes energy use. Waste management and noise pollution are also considered. The discussion will explore sustainable airport performance. It will examine how airports measure their sustainability efforts. It focuses on improvement and the benefits of sustainable commitment in airport operations. Drawing from relevant literature, this study enhances existing work. The study encourages future research by identifying priority areas regarding sustainable airport commitment and contributing to sustainable airport performance.